2015
DOI: 10.1016/j.neuroscience.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the rapid and the sustained antidepressant-like effects of ketamine in stress-naïve and “depressed” mice exposed to chronic mild stress

Abstract: During the past decade, one of the most striking discoveries in the treatment of major depression was the clinical finding that a single infusion of a sub-anesthetic dose of the N-methyl-d-aspartate receptor antagonist ketamine produces a rapid (i.e. within a few hours) and long-lasting (i.e. up to two weeks) antidepressant effect in both treatment-resistant depressed patients and in animal models of depression. Notably, converging clinical and preclinical evidence support that responsiveness to antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 58 publications
12
143
0
2
Order By: Relevance
“…Increased latency to groom and reduced total grooming time in the sucrose ST is representative of the core symptom of depression, anhedonia. These results show some similarity to earlier results indicating that the antidepressant potential of ketamine was longer lasting in males, as assessed in the ST [38]; however, our ST results contradict other studies that report that either both sexes or only female mice are susceptible to ST. These discrepancies between various studies may be related to strain differences, as mentioned above.…”
Section: Discussionsupporting
confidence: 89%
“…Increased latency to groom and reduced total grooming time in the sucrose ST is representative of the core symptom of depression, anhedonia. These results show some similarity to earlier results indicating that the antidepressant potential of ketamine was longer lasting in males, as assessed in the ST [38]; however, our ST results contradict other studies that report that either both sexes or only female mice are susceptible to ST. These discrepancies between various studies may be related to strain differences, as mentioned above.…”
Section: Discussionsupporting
confidence: 89%
“…[54] These results are in agreement with other studies utilizing a 10-or 12-day dosing regimen to establish longer-lasting effects of chronic ketamine on depressive-like activity in the FST. [55,56] In the literature, there are significant dose, gender and strain-dependent differences in the sensitivity to ketamine treatment. For example, Wistar rats are insensitive to the antidepressant-like effects of low dose ketamine (2.5 and 5 mg/kg) in comparison to Wistar-Kyoto rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although female mice were shown more reactive to the earlier effects of ketamine, the antidepressant potential of this drug was proved to last longer in male animals. [56] A recent clinical study suggested that sex differences in glutamate receptor gene expression might also play a major role in depression and antidepressant efficacy of drugs. [3] In a large cohort of postmortem subjects from MDD patients and controls, more generalized and severe disruption in the regulation of the glutamate receptors were found in females, but more specific alterations were reported in males.…”
Section: Discussionmentioning
confidence: 99%
“…Each rat was first placed in the central zone of the EPM with its head oriented to the closed arm. The rat was allowed to freely explore the maze for 5 min as described previously (Franceschelli, Sens, Herchick, Thelen, & Pitychoutis, 2015;Suo et al, 2013) …”
Section: Elevated Plus Maze Testmentioning
confidence: 99%